2-Carba-lysophosphatidic acid is a novel β-lysophosphatidic acid analogue with high potential for lysophosphatidic acid receptor activation and autotaxin inhibition - Fukasawa, Keiko; Gotoh, Mari; Uwamizu, Akiharu; Hirokawa, Takatsugu; Ishikawa, Masaki; Shimizu, Yoshibumi; Yamamoto, Shinji; Iwasa, Kensuke; Yoshikawa, Keisuke; Aoki, Junken; Murakami-Murofushi, Kimiko (Scientific reports, 2021)
Cyclic phosphatidic acid (cPA) is a naturally occurring phospholipid mediator that, along with its chemically stabilized analogue 2-carba-cyclic phosphatidic acid (2ccPA), induces various biological activities in vitro and in vivo. Although cPA is similar to lysophosphatidic acid (LPA) in structure and synthetic pathway, some of cPA biological functions apparently differ from those reported for LPA. We previously investigated the pharmacokinetic profile of 2ccPA, which was found to be rapidly degraded, especially in acidic conditions, yielding an unidentified compound. Thus, not only cPA but also its degradation compound may contribute to the biological activity of cPA, at least for 2ccPA. In this study, we determined the structure and examined the biological activities of 2-carba-lysophosphatidic acid (2carbaLPA) as a 2ccPA degradation compound, which is a type of β-LPA analogue. Similar to LPA and cPA, 2carbaLPA induced the phosphorylation of the extracellular signal-regulated kinase and showed potent agonism for all known LPA receptors (LPA 1–6 ) in the transforming growth factor-α (TGFα) shedding assay, in particular for LPA 3 and LPA 4 . 2carbaLPA inhibited the lysophospholipase D activity of autotaxin (ATX) in vitro similar to other cPA analogues, such as 2ccPA, 3-carba-cPA, and 3-carba-LPA (α-LPA analogue). Our study shows that 2carbaLPA is a novel β-LPA analogue with high potential for the activation of some LPA receptors and ATX inhibition.